The Outdoor Girls in Florida; Or, Wintering in the Sunny South - Hope, Laura Lee (Salt Lake City, UT : Project Gutenberg, 2006)
"The Outdoor Girls in Florida; Or, Wintering in the Sunny South" by Laura Lee Hope is a novel written in the early 20th century. The story follows a group of four adventurous girls$1 (BGrace, Betty, Mollie, and Amy$1 (Bas they embark on a winter trip from their home in Deepdale to sunny Florida. The narrative revolves around their experiences, challenges, and the lingering concern over Grace's missing brother Will, setting a backdrop of camaraderie and exploration amid the tranquility of the Florida landscape. At the start of the story, the girls are introduced in a state of anxiety due to the sudden disappearance of Grace's brother, Will, who has run away from his job at a cotton mill in Atlanta. As the group gathers to comfort Grace and discuss the disheartening news, the girls also contemplate an invitation to visit Amy's uncle's orange grove in Florida, which ignites their spirits amidst the turmoil. Shortly after receiving a letter from Will indicating he has started a new life in Jacksonville, another telegram comes with ominous news suggesting his whereabouts are unknown again. Thus, the plot sets off on a dual journey of support for their friend while they also traverse the excitement and challenges of their anticipated adventure in the South. (This is an automatically generated summary.)s
Release date is 2006-09-17
E-text prepared by Marilynda Fraser-Cunliffe, Emmy, and the Project Gutenberg Online Distributed Proofreading Team
Keywords: Adventure and adventurers -- Juvenile fiction; Girls -- Juvenile fiction; Girls -- Societies and clubs -- Juvenile fiction; Florida -- Juvenile fiction